Designer polyQ fusion proteins sequester USP7/HDM2 for modulating P53 functionality - Xiang-Le Zhang; Hong-Wei Yue; Ya-Jun Liu; Jian-Yang Wang; Heng-Tong Duan; Yin-Hu Liu; Lei-Lei Jiang; Hong-Yu Hu (iScience)
Summary: Overexpression of USP7 and HDM2 inactivates P53 signaling in tumor cells and facilitates their progression, but suppression of these targets by conventional strategies to reactivate P53 function remains a challenge. We applied polyQ sequences and target-interacting peptides to engineer polyQ fusion proteins that specifically sequester the targets, hence depleting their availabilities and modulating the P53 functionality. We have revealed that the designer fusion Atx793Q-N172-IRF (IRF sequence: SPGEGPSGTG) sequesters USP7 and/or HDM2 into aggregates and thereby increases the P53 level, but it depends on the IRF repeats fused, suggesting that depletion of the USP7 availability plays a dual role in controlling P53 stability. Direct sequestration of HDM2 by Atx793Q-N172-PMI (PMI: TSFAEYWNLLSP) remarkably reduces the protein level of soluble HDM2 and hence increases the P53 level, which consequently up-regulates expression of the downstream genes. The polyQ-fusion strategy is feasible to modulate the P53 stability and functionality, furnishing a therapeutic potential for cancers.